ONLINE CONSULTATION EFFECTIVENESS IN COMMUNITIES AND DATA PROTECTION REGULATION DURING COVID-19 PANDEMIC - Irsan Irsan; M Rasyid; Meria Utama (Fakultas Kedokteran Universitas Sriwijaya, 2023)
All countries in the world have faced a global pandemic called the Coronavirus or SARS-CoV-2. Indonesian Government has implemented several policies such as by regulating the social distancing. The community was also asked by the government to avoid hospital visits and switch to using telemedicine services. To date there have been reported increases in the use of telemedicine services in the community during the COVID-19 pandemic. This research is cross sectional study using an online survey method. Primary data were collected using google form questionnaire. This study consisted of 155 respondents who are using online consultation services during the COVID-19 pandemic and willing to be the subject of this research. Out of 155 respondents which fulfilled the inclusion criteria, the result showed that the respondents are dominated by female (51 aged 22 years old (25,2%), from South Sumatera (59,4%), last education college or equivalent (76,1%), using private telemedicine (60,6%). Respondents claimed that the operation of telemedicine or online consultation services was normal (52.9%) and satisfied (62.6%). Online consultation or telemedicine is considered effective as a digital health service measured by the satisfaction of the Indonesian people during the COVID-19 pandemic. (p = <0,0001. The result also showed that Indonesia regulates the protection of the citizens data of in the constitution 1945 particularly in Article 28G (1) that each person shall have the right their personal selves protected, families, respect, dignity, and possessions under their control. Indonesia enacted on 2022, a specific law stipulated personal data protection, i.e., Law No. 27 of 2022 regarding Personal Data Protection. Before, the previous regulatory regime that focused on personal data processed through an electronic system, currently it applies to personal data processed by both electronic and non-electronic means.